Implementing The Problem-Based Learning Model In The Vuca Era To Enhance Student Competencies - Elfira Elfira (Yayasan Abdurrauf Cendekia Nusantara, 2026)
The rapid, unpredictable shifts of the VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) era necessitate a profound paradigm shift in educational frameworks away from rote memorization toward adaptive competence. Purpose of the Study: This study explores how the implementation of the Problem-Based Learning (PBL) model can effectively prepare and equip students with the critical cognitive and moral competencies required to thrive in the VUCA era. Methods: Using a qualitative library research method, a systematic analysis of authoritative books, literature, and peer-reviewed journals was conducted to synthesize the strategic intersection between PBL implementation, cognitive scaffolding, and national character education. Results: The findings reveal that PBL acts as a crucial procedural process where students construct contextual knowledge by resolving authentic, ill-structured problems. Furthermore, in the uncertainty of the VUCA landscape, the strategic application of dynamic scaffolding (combining adding and fading) enhances self-directed learning. Integrating localized character development, such as Pancasila values and national ideology, into the PBL framework is essential for filtering information overload and countering moral degradation, thereby producing graduates who are both intellectually capable and ethically grounded.